2021
DOI: 10.1364/optica.426674
|View full text |Cite
|
Sign up to set email alerts
|

How large is the quantum enhancement of two-photon absorption by time-frequency entanglement of photon pairs?

Abstract: We present a theoretical proof that the “quantum enhancement” of two-photon absorption, thought to be a means to improve molecular spectroscopy and imaging, is tightly bounded by the physics of photonic entanglement and nonlinear response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…it creates a molecular excitation, and we have dropped the spatial dependence of the operators. A detailed account for the derivation of the ETPA probability can be found, e.g., in [49,52]. Here, we only present the final result which, neglecting the polarization degrees of freedom at first, reads…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…it creates a molecular excitation, and we have dropped the spatial dependence of the operators. A detailed account for the derivation of the ETPA probability can be found, e.g., in [49,52]. Here, we only present the final result which, neglecting the polarization degrees of freedom at first, reads…”
Section: The Modelmentioning
confidence: 99%
“…In theoretical work, recent analyses predict a very small enhancement of the ETPA cross section due to spectral entanglement [48,49]. The key assumption in these publications is that molecular resonances are broadened much more strongly than their atomic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…These promising features have sparked a lot of interest in two-photon EPPs interaction (EPPI) [6][7][8][9][10]. However, recent studies have shown that, due to the weakness of two-photon interactions and the low EPPs flux in the single-pair regime, EPPI with matter is expected to be around the noise limit of common systems [11][12][13]. This limitation gives rise to a need for improving the employed techniques for EPPI and optimizing the properties of the interaction medium.…”
Section: Introduction Nergy-time Entangled-photon Pairsmentioning
confidence: 99%
“…However, the magnitude of this enhancement has been questioned by recent experiments 17−22 and theoretical analysis. 23,24 Entangled two-photon absorption (ETPA) has been applied for electronic state characterization 25,26 but so far has not been demonstrated for detecting electron-nuclear wavepacket dynamics. The passage through conical intersections (CIs) 27 is a ubiquitous example of ultrafast dynamics in molecules.…”
mentioning
confidence: 99%
“…For example, two-photon absorption of time–energy entangled photons contains many nonclassical features and functionalities, including linear rather than quadratic scaling with the pump intensity, observing classically forbidden transitions, , suppressing classical one-photon resonant peaks, and manipulating excitation pathways. , A nearly 10 orders of magnitude enhancement of the two-photon absorption rate by entangled photons over classical light at the same photon fluxes has been reported, thus reducing the risk of photodamage of biological samples. However, the magnitude of this enhancement has been questioned by recent experiments and theoretical analysis. , …”
mentioning
confidence: 99%